Performance prediction of Olympic rowing boats accounting for full dynamics - Mola, A.; Del Grosso, L.; Formaggia, L.; Miglio, E. (Communications to SIMAI Congress, 2006)
The periodic forces imposed at the oars and due to the movement of the rowers induce on the boat secondary motions causing an additional drag which may represent a significant part of total dissipated energy. We have taken the approach of computing the complete scull motion including pitching, vertical and horizontal movement. A full dynamic model requires simulating rowers inertial forces, thrust forces at the oarlocks and fluid-dynamic forces. It is a complex fluid-structure interaction problem that we analyzed by coupling different fluid dynamic models with a dynamic model of the boat. We will therefore compare the results obtained using these alternatives.